1997
DOI: 10.1243/0959651971539777
|View full text |Cite
|
Sign up to set email alerts
|

Pressure pulsations in reciprocating pump piping systems Part 2: Experimental investigations and model validation

Abstract: This paper reports on a series of laboratory tests on two reciprocating pump systems. Factors affecting pressure and flow pulsation characteristics are discussed. Measured time-domain characteristics, under non-cavitating and cavitating conditions, are compared with predictions from the computer model developed in Part 1 of this paper. Generally, good agreement is achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…The reason for this is that PD pumps are very difficult to model. This was proved in the technical literature by many authors such as Johnston [9], Edge [10], [11], and Iannetti [1]. The numerical methods which are used, especially in the research environment and sometimes in industry, are CFD based methodologies and lumped parameters analytical methods.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The reason for this is that PD pumps are very difficult to model. This was proved in the technical literature by many authors such as Johnston [9], Edge [10], [11], and Iannetti [1]. The numerical methods which are used, especially in the research environment and sometimes in industry, are CFD based methodologies and lumped parameters analytical methods.…”
Section: Introductionmentioning
confidence: 95%
“…This highlights the importance of finding alternative tools. Simplified analytic methods were developed in times when the scarce computational power available gave no other option to researchers such as Johnston [9] and Edge [10], [11]. These methods consider every item composing a pumping system as a lumped parameter where the information of its influence on the overall system is concentrated in a parametric function.…”
Section: Introductionmentioning
confidence: 99%
“…Budny et al [7] performed the experiment to test the structural pipeline damping, and the results showed that the structural damping could accelerate the fluid transient decay obviously. Edge et al [8] conducted the test rig to investigate pressure pulsation characteristics in reciprocating pump pipeline system, and the results showed that the pressure pulsation was dependent on the pump speed. Adamkowski et al [9] conducted a special test rig to test the effect of elastic support onto fluid transients and water hammer.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the modeling of a reciprocating pump or reciprocating compressor includes the models on piston motion, variation of cylinder pressure, inclusion of cavitation, valve motion, thermodynamic, and heat transfer in evaluating the performance of the pump [80][81][82][83][84]. Some special modeling such as pressure pulsation modeling due to the reciprocating motion has also been carried out in examining the flow characteristics on reciprocating pumps [85,86]. [85] In 1984, Edge [81] developed a digital computer model of a multi-cylinder piston pump with self-acting valves.…”
Section: Mathematical Modelmentioning
confidence: 99%